EFEKTIVITAS PEMBERIAN PENGUATAN BERKEARIFAN LOKAL TERHADAP MOTIVASI BELAJAR ILMU PENGETAHUAN SOSIAL(IPS) SISWA DI KELAS III SD ISLAM DATOK SULAIMAN BAGIAN PUTRI PALOPO - Darnia Darnia (Pedagogik Journal of Islamic Elementary School, 2019)
This study aims to determine the provision of strengthening local wisdom and knowing the motivation to learn Social Sciences (IPS) students in the subject matter of the natural environment and the artificial environment through the provision of local wisdom strengthening in class III SD Islam Datok Sulaiman Palopo. This study uses a type of experimental research with a design or design Quasi Experimental Design using the research technique Nonequivalent Control Group Design. Data in the study were collected using observation, testing, and documentation techniques. The results of this study indicate that the provision of local wisdom reinforcement is effective for increasing students' learning motivation in Social Sciences. It is evident from the results of descriptive statistical analysis that the average score of Social Sciences learning outcomes of experimental class students is 81.03 while the average score of the learning outcomes of the control class is 66.81. The results of inferential statistical analysis obtained zhit = 3.92 with a significant level of 5% obtained ztab = 1.64 means zhit > ztab which causes H0 to be rejected and H1 accepted. This shows that the learning motivation of Social Sciences students whose learning applies local wisdom reinforcement is better than the learning motivation of Social Sciences students who study without applying the provision of local wisdom. Thus, the provision of strengthening local wisdom is one of the effective ways to increase students' learning motivation in Social Sciences.